Neuromodulatory Correlates of Pupil Dilation - Larsen, Rylan S.; Waters, Jack (Frontiers in Neural Circuits, 2018)
Pupillometry has long been used as a measure of brain state. Changes in pupil diameter are thought to coincide with the activity of neuromodulators, including noradrenaline and acetylcholine, producing alterations in the brain state and corresponding changes in behavior. Here we review mechanisms underlying the control of pupil diameter and how these mechanisms are correlated with changes in cortical activity and the recruitment of neuromodulatory circuits.